Wheat Improvement, Management and Utilization 2017
DOI: 10.5772/67116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Growth Habit and Architecture Genes on Adaptation and Performance of Bread Wheat

Abstract: In bread wheat (Triticum aestivum L.), flowering time and plant stature are important phenological and agronomic traits for adaptation, yield potential, and yield stability. Timely flowering is critical for production, and the flowering window has to be late enough to avoid early season frosts but early enough to avoid late season stresses such as heat and terminal drought. Flowering time is controlled mainly by vernalization, photoperiod response, and earliness per se genes, which can be exploited to fine-tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…[ 20,21 ] The difference in flowering and ripening time, which is mainly caused by the growth habit, should be considered as important in preventing grain ripening under unfavorable environmental conditions that involve α‐amylase activity. [ 22,23 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20,21 ] The difference in flowering and ripening time, which is mainly caused by the growth habit, should be considered as important in preventing grain ripening under unfavorable environmental conditions that involve α‐amylase activity. [ 22,23 ]…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] The difference in flowering and ripening time, which is mainly caused by the growth habit, should be considered as important in preventing grain ripening under unfavorable environmental conditions that involveamylase activity. [22,23] From an enzymological point of view, the enzyme as a catalyst is strongly dependent on the medium conditions (i.e., pH, temperature, substrate concentrations, etc.) which could modify its catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, this stress can manifest itself at an early stage ( Kumar et al, 2021 ). Three gene groups, including Vrn , Ppd , and Eps , have a major influence on heading and flowering time of wheat ( Snape et al, 2001 ; Distelfeld et al, 2009 ; Kumar et al, 2012 ; Khumalo et al, 2017 ). Early studies reported that the switch from vegetative to reproductive development is promoted by the prolonged cold temperatures of winter (vernalization) ( Chouard, 1960 ).…”
Section: Introductionmentioning
confidence: 99%